Advancements in thermoelectric generators for enhanced hybrid photovoltaic system performance. (July 2019) - Shittu, Samson; Li, Guiqiang; Akhlaghi, Yousef Golizadeh; Ma, Xiaoli; Zhao, Xudong; Ayodele, Emmanuel
Abstract: Effective thermal management of photovoltaic cells is essential for improving its conversion efficiency and increasing its life span. Solar cell temperature and efficiency have an inverse relationship therefore, cooling of solar cells is a critical research objective which numerous researchers have paid attention to. Among the widely adopted thermal management techniques is the use of thermoelectric generators to enhance the performance of photovoltaics. Photovoltaic cells can convert the ultra-violent and visible regions of the solar spectrum into electrical energy directly while thermoelectric modules utilize the infrared region to generate electrical energy. Consequently, the combination of photovoltaic and thermoelectric generators would enable the utilization of a wider solar spectrum. In addition, the combination of both systems has the potential to provide enhanced performance due to the compensating effects of both systems. The waste heat produced from the photovoltaic can be used by the thermoelectric generator to produce additional energy thereby increasing the overall power output and efficiency of the hybrid system. However, the integration of both systems is complex because of their opposing characteristics thus, effective coupling of both systems is essential. This review presents the concepts of photovoltaics and thermoelectric energy conversion, research focus areas in the hybrid systems, applications of such systems, discussion of the most recent research accomplishments and recommendations for future research. All the essential elements and research areas in hybrid photovoltaic/thermoelectric generator are discussed in detailed therefore, this review would serve as a valuable reference literature. Highlights: A detailed review of photovoltaic thermal management is presented. The role of thermoelectric generator in hybrid photovoltaic enhancement is explained. Research focus areas in hybrid photovoltaic/thermoelectric generator are discussed. Recommendations for future research on hybrid PV/TEG are presented.